Models of kulture in Nabokov's memoirs and translation memoirs in Serbian and Croatian language - Razdobudko-Čović Larisa I. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2012)
The paper presents an analysis of two Serbian translations of V. Nabokov's memoirs, that is the translation of the novel 'Drugie berega' ('The Other Shores') published in Russian as an authorized translation from the original English version 'Conclusive Evidence', and the translation of Nabokov's authorized translation from Russian to English entitled 'Speak, Memory'. Creolization of three models of culture in translation from the two originals - Russian and English - Is presented. Specific features of the two Serbian translations are analyzed, and a survey of characteristic mistakes caused by some specific characteristics of the source language is given. Also, Nabokov's very original approach to translation which is quite interpretative is highlighted.